Дослідження адаптивних методів подавлення шуму в відеозображеннях - Клюшенков, Р. О. (My University, 2020)
In this paper we investigate some noise filtering methods on real video images. The study was conducted by mathematical simulation. For the experiment we used digital video images with a high signal-to-noise ratio. Than we simulated Gaussian white noise with different dispersion. Investigated spatial and temporal filtering methods: averaging filter with a rectangular window, median filter, time averaging filter. Size of the filter window was adaptive to noise dispersion. Estimation of signal-to-noise ratio was obtained. Deviation of estimates did not exceed 3 dB.
I
Keywords: відео; медіанний фільтр; шумоподавлення